The influence of natural functional clothing on some biophysical parameters of the skin. Issue 8 (April 2019) - Zimniewska, Malgorzata; Pawlaczyk, Mariola; Krucinska, Izabella; Frydrych, Iwona; Mikolajczak, Przemysław; Schmidt-Przewozna, Katarzyna; Komisarczyk, Agnieszka; Herczynska, Lucyna; Romanowska, Barbara
The objectives of the study were to develop functional natural fiber clothing with microcapsules containing active herbal extracts with properties enhancing the treatment of dermatoses and to confirm the efficiency of the clothing's activity by testing its effect on the biophysical parameters of human skin. As a result of the work, clothing enriched with green tea and Viola tricolor extracts enclosed in ethyl cellulose microcapsules was produced. The microcapsules were applied on the inner surface of linen knitted fabric, which ensured direct contact of the active substances with the patients' affected skin. The efficiency of the clothing was tested according to our own methodology, which included wearing tests, microbiological tests of the skin and tests of skin moisture, transepidermal water loss and itching intensity. Also, the effect of the active substances present on the fabrics on the in vitro culture of human keratinocytes was evaluated. The test results confirmed that linen clothing enriched with medicinal plant extracts enclosed in microcapsules had an effect on the reduction of itching intensity, an increase in skin moisture, reduction of transepidermal water loss and a reduction of pathogenic bacterial colonies residing on the patients' skin. They confirmed that the new method of administering herbal substances to the skin of dermatological patients via the wearing of functional clothing is effective and leads to symptom relief. The studies allowed for the filing of a patent submission, number P 411869, titled "The clothing acting as a dressing supplement in the therapy of dermatological diseases."